(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study describes the self-care practices of heart failure patients at Vinmec Times City International Hospital in 2023. Methods: A cross-sectional descriptive study was conducted on 246 outpatients diagnosed with heart failure at the Cardiology Department of Vinmec Times City International Hospital from April 2023 to October 2023. The SCHFI V6.2 questionnaire was used to assess patients’ self-care practices. Results: The proportion of heart failure patients achieving adequate self-care practices was very low across all three domains: 7.3% in maintenance care, 4.2% in management care, and 3.3% lacked confidence in performing self-care activities. Younger patients (< 60 years old) (OR = 1.8), males (OR = 2.1), post-secondary education (OR = 3.4), and those with two or more comorbidities (OR = 1.8) demonstrated better self-care practices than other groups (p < 0.05). Conclusion: The self-care practices of heart failure outpatients at Vinmec Times City International Hospital remain relatively low. Self-care practices were associated with age, gender, education level, and the presence of two or more comorbidities. It is essential to explore psychological barriers, motivation, and family conditions to develop individualized support measures for each patient.